2003
DOI: 10.1172/jci200316923
|View full text |Cite
|
Sign up to set email alerts
|

Osteopetrosis and thalamic hypomyelinosis with synaptic degeneration in DAP12-deficient mice

Abstract: Deletions in the DAP12 gene in humans result in Nasu-Hakola disease, characterized by a combination of bone fractures and psychotic symptoms similar to schizophrenia, rapidly progressing to presenile dementia. However, it is not known why these disorders develop upon deficiency in DAP12, an immunoreceptor signal activator protein initially identified in the immune system. Here we show that DAP12-deficient (DAP12–/–) mice develop an increased bone mass (osteopetrosis) and a reduction of myelin (hypomyelinosis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 37 publications
1
71
4
Order By: Relevance
“…Osteoclasts are differentiated from hematopoietic precursors of the monocyte/macrophage lineage by stimulation with a tumor necrosis factor family cytokine, receptor activator of nuclear factor κB ligand (RANKL) and macrophage colony‐stimulating factor (M‐CSF). Because these two cytokines induce osteoclasts in vitro, they were thought to be sufficient for osteoclastogenesis, but recent studies demonstrated that osteoclastogenesis also requires immunoreceptor tyrosine‐based activation motif (ITAM) signaling …”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts are differentiated from hematopoietic precursors of the monocyte/macrophage lineage by stimulation with a tumor necrosis factor family cytokine, receptor activator of nuclear factor κB ligand (RANKL) and macrophage colony‐stimulating factor (M‐CSF). Because these two cytokines induce osteoclasts in vitro, they were thought to be sufficient for osteoclastogenesis, but recent studies demonstrated that osteoclastogenesis also requires immunoreceptor tyrosine‐based activation motif (ITAM) signaling …”
Section: Introductionmentioning
confidence: 99%
“…The 2 ITAMcontaining adapters, Dap12 and the γ chain of Fc receptor (FcRγ), have a profound impact on OCs by modulating RANKL-mediated calcium influx and NFATc1 expression. In humans, mutation in the Dap12 gene is responsible for Nasu-Hakola disease, characterized by multiple bone cysts associated with a unique form of neurodegeneration (21). Deletion of Dap12 and FcRγ (Dap12 -/-FcRγ -/-), in mice, leads to severe osteopetrosis due to defective OC development (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, mutation in the Dap12 gene is responsible for Nasu-Hakola disease, characterized by multiple bone cysts associated with a unique form of neurodegeneration (21). Deletion of Dap12 and FcRγ (Dap12 -/-FcRγ -/-), in mice, leads to severe osteopetrosis due to defective OC development (20)(21)(22). In vitro triggering of either receptor by crosslinking with an antibody accelerates RANKL-induced OC differentiation (23).…”
Section: Introductionmentioning
confidence: 99%
“…Takai and colleagues also demonstrate that DAP12 is expressed in normal oligodendrocytes and microglial cells (3). Oligodendrocytes form the myelin sheath that wraps around neural axons, enhancing nerve signal conductance in the CNS and ensuring axonal integrity.…”
Section: Dap12 As Critical Regulator Of Osteoclasts and Oligodendrocytesmentioning
confidence: 99%
“…The study by Takai et al shows that DAP12 protein is expressed in normal osteoclasts (3). These are polykarions of the monocyte/macrophage lineage that specialize in bone resorption (9).…”
Section: Dap12 As Critical Regulator Of Osteoclasts and Oligodendrocytesmentioning
confidence: 99%